IMF Survey, Volume 37, Issue 12. (IMF Survey; IMF Survey ;, 2008)
Global financial crisis, Iceland, Poul Thomsen, IMF work program, IMF Shocks Facility, Kyrgyz Republic; Malawi; Exogenous Shocks Facility, Pakistan loan, IMF and social safety nets, gains against poverty in jeopardy, commodity prices slump, Latin America withstands shocks, Improved policies help Latin America, Asian Regional Outlook, Bosnia and Herzegovina, news briefs.